Sıngle Jaw Bıcuspıd Extractıons And Functıonal Occlusıon - Eray Erdoğan (Galenos Yayinevi, 1995)
The principle of the orthodontic approaches called therapeutic class II or III is to compensate the mild or moderate skeletal and/or dentoalveolar malocclusions with dental correction by the extraction of the bicuspids bilaterally in one jaw. The main purpose of these interventions where the molars are positioned in class II or III, is to have rapidly a functional occlusion in the patients with an ideal interincisal and intercanine relation. Non-anatomic posterior dental relations oblige orthodontist to have some precautions in the different phases of the treatment. The residual posterior interferences not been able to be solved in the finishing phase should be eliminated by grinding according to gnathologic records.